The Correlation of Waist-to-Hip Ratio and Sleep Quality with Fasting Blood Glucose in Type 2 Diabetes Mellitus Patients - Arif Budi Santoso; Kezia Elian Devina; Dyah Ayu Kusuma Wardani (Universitas Islam Negeri Walisongo Semarang, 2025)
Type 2 diabetes mellitus (T2DM) is characterized by uncontrolled blood sugar levels and is diagnosed using fasting blood glucose (FBG) measurements. Risk factors for T2DM include central obesity, measured by the waist-to-hip ratio (WHR), and poor sleep quality. This study aimed to determine the relationship between WHR and sleep quality with FBG levels in T2DM patients, by employing an observational study with a cross-sectional design A total of 51 respondents aged 45–75 years were selected using purposive sampling. Waist and hip circumference were measured with a metline; sleep quality was assessed using a Pittsburgh Sleep Quality Index (PSQI) questionnaire, and FBG levels were obtained from secondary data in the form of medical records at the Karangmalang Community Health Center. Spearman was used for the bivariate test, while the multiple linear regression was used for the multivariate test. The test results showed a significant relationship between WHR and FBG levels (p=0.001, r=0.460), and between sleep quality with FBG levels (p<0.001, r=0.553). Multivariate results obtained p=0.026 for sleep quality and p=0.093 for WHR, suggesting sleep quality is more strongly associated with FBG levels. Sleep quality was the dominant factor associated with FBG levels in T2DM patients. The results of this study can be used as a guideline for individuals with T2DM to maintain normal blood glucose levels and good sleep quality for better blood glucose control.